Diamonds on the soles of their feet: groundwater monitoring in the Hout Catchment, South Africa - Goldin, J.; Mokomela, R.; Kanyerere, T.; Villholth, Karen G. (SAGE Publications, 2021)
With the impulse to control and order the disorderly, the threads or tributaries of affect and emotion, which mimic the meanderings of the aquifer itself, are often oversimplified or ignored. These are not anomalies of citizen science (CS) but ‘normal’ and expected ‘disconnects’ that surface when working within a multidisciplinary environment. The article adds value to current discourse on CS by reflecting on the confusing configurations and shifting allegiances that are part and parcel of CS experience. In presenting research from a current project in the Hout Catchment, Limpopo Province in South Africa, it suggests that CS is often oversimplified and does not capture the array of emotions that emerge at multiple scales around CS projects. The authors reflect on the field, which is fraught, fragile and fleeting—and on the intrusions into the field—similar itself to an aquifer with its dykes and flows. Considering CS within the frame of feminist philosophy, it is emancipatory and personally transformative with the element of ‘surprise’ that the end point is undetermined—and the process, however much ‘planned’ is unknown. CS in this instance is a powerful tool for creating virtuous cycles of inclusion and equality and promoting sustainable development through improved water literacy through a grassroot, out-of-the-classroom pedagogy.